2019
DOI: 10.2196/12632
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Youth and Transition to Further Education, Training, and Employment in Australia: Protocol for a Mixed Methods Study

Abstract: BackgroundYoung people with refugee experiences are widely acknowledged as encountering multiple disadvantages that affect their school completion and retention, university entry, and subsequent employment. This paper discusses the rationale for and protocol of a mixed methods investigation focusing on improving education and employment outcomes among refugee background youth aged 15 to 24 years from three focus regions: the Middle East (Afghanistan, Iran, Iraq, Syria), South Asia (Nepal, Bhutan, Myanmar/Burma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Data were collected collaboratively with support from the research team, industry partners, and bilingual workers. Details of this research project and the collaborative data collection process can be found in other publications [ 57 , 58 ]. In brief, data were collected in South Australia throughout 2017–2018: youth participants were presented with a survey in a paper format and were supported through informed consent processes by bilingual workers and/or interpreters where relevant.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected collaboratively with support from the research team, industry partners, and bilingual workers. Details of this research project and the collaborative data collection process can be found in other publications [ 57 , 58 ]. In brief, data were collected in South Australia throughout 2017–2018: youth participants were presented with a survey in a paper format and were supported through informed consent processes by bilingual workers and/or interpreters where relevant.…”
Section: Methodsmentioning
confidence: 99%
“…Refugeebackground youth are often managing educational disturbances, a greater burden of caring or helping in their families which often includes supporting parents with childcare and translating for them at appointments (Changemakers Refugee Forum et al, 2011;Humpage, 2009;James, 2013), and coping with separation, loss or trauma (Cerna, 2019). They may also be adapting to a new education system, and an unfamiliar language and culture (Ziaian et al, 2019).…”
Section: Key Factors Influencing Positive Youth Development For Migra...mentioning
confidence: 99%
“…Poverty is a barrier to participation in activities that support PYD for refugee-background youth (Block & Gibbs, 2017;Child Wellbeing and Poverty Reduction Group, 2019;Deng & Marlowe, 2013;O'Connor, 2014;Willette, 2020) and reinforces social exclusion (Child Wellbeing and Poverty Reduction Group, 2019). For example, when researching refugee-background youth in Australia, Ziaian et al, (2019) found poverty had a greater impact than trauma on pathways to tertiary education or employment.…”
Section: Belonging and Participationmentioning
confidence: 99%
See 2 more Smart Citations